Kajian Pendidikan Vokasi Lanjutan Jalur RPL Type A1 Kelas Kerjasama Politeknik Penerbangan Makassar dengan Politeknik Negeri Ujung Pandang - Bahrawi, Ahmad; Sabur, Fatmawati; Firman; Aprilianus, Tomy (Politeknik Penerbangan Makassar, 2021)
The purpose of this study was to evaluate the past learning recognition program (RPL) type A1 as an option due to the unavailability of Diploma IV study programs in seven UPT Air Transportation, so that the achievement of graduate absorption can be realized and the value of unemployment can be suppressed by developing appropriate student competencies. with the basic competencies obtained at the diploma III education level. To obtain data and information based on an empirical description of the collaborative class RPL program evaluation study for boarding education graduates using the CIPP method. Research Results The implementation of level transfer from the D.III program with a boarding system education pattern for the Airport Technology and Air Navigation Technology study program to the D.IV program through the RPL type A1 route by applying the Blended Learning and non-boarding learning methods in the Mechatronics and Engineering study program Electricity, can be implemented by taking education as much as 33 - 42 credits. The number of practice credits is adjusted to the fulfillment of learning outcomes from each study program and the equalization of the curriculum from the D.III level of the Makassar Aviation Polytechnic is recognized as 100% to be able to continue education over the level to D.IV of the Ujung Pandang State Polytechnic.